Defeating authoritarian leaders in postcommunist countries - Bunce, Valerie 1949- (Cambridge studies in contentious politics, 2011)
Machine generated contents note: Part I. The Puzzle: 1. Breakthrough elections: mixed regimes, democracy assistance, and international diffusion; 2. Electoral stability and change in mixed regimes; Part II. Case Studies: 3. The 1998 election in Slovakia and the 2000 election in Croatia: model solidifies and is transferred; 4. Defeating a dictator at the polls and in the streets: the 2000 Yugoslav election; 5. Ukraine: the orange revolution; 6. Georgia and Kyrgyzstan: fraudulent parliamentary elections, mass protests, and presidential abdications; 7. Failed cases: Armenia, Azerbaijan and Belarus; Part III. Comparative Analyses: 8. Explaining divergent electoral outcomes: regime strength, international democracy assistance, and electoral dynamics; 9. The electoral model: evolution and elements; 10. The cross-national diffusion of democratizing elections; 11. After the elections: explaining divergent regime trajectories; 12. Conclusions: democratizing elections, international diffusion and U.S. democracy assistance